42‐3L: Late‐News Paper: Development of Crystalline IGZO and LTPS Hybrid TFTs Array Technology. Issue 1 (May 2017) - Ye, Jia-Hong; Huang, Ching-Liang; Chen, Ming-Yao; Chen, Pei-Ming; Huang, Kuo-Yu; Peng, Chia-Tien; Huang, Wei-Ming; Wu, Yang-An
Abstract : Because of the unique property, the low leakage current of crystalline indium gallium zinc oxide (c‐IGZO) thin film transistors (TFTs), it can archive the low power consumption of a panel within low frame rate driving. Low temperature poly‐silicon (LTPS) TFTs as components of shift register circuit can fulfill small border size. The c‐IGZO TFTs for pixel switch and the LTPS TFTs for gate driver on array backplane have been both deposited on glass substrate. We demonstrate a prototype of 1.4 inch circular LCD with c‐IGZO and LTPS hybrid backplane technology to achieve small border size and low power consumption. And the panel shows good picture quality without flickering when very low frame rate driving (6Hz). In addition, the optical property and crystallinity of c‐IGZO have been studied in this work.